2013
DOI: 10.3329/bjb.v42i1.15802
|View full text |Cite
|
Sign up to set email alerts
|

Location and chemical composition of semi-permeable layer of forage seeds

Abstract: The presence of the semi-permeable layer is determined in Roegneria nutans (Keng.) Keng, Achnatherum inebrians (Hance.) Keng, Hordeum vulgare var. nudum Hook. f., Triticale, Festuca sinensis Keng., and Bromus inermis Leyss. using the lanthanum nitrate tracer method, transmission electron microscopy and energy dispersive X-ray analysis. It was an amorphous membranous structure firmly attached on the external portion of the seed coat. The diversified chemical composition of the semi-permeable layer of the specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The semipermeable layer is firmly attached on the external portion of the seed coat in Roegneria nutans , Achnatherum inebrians , Hordeum vulgare var. nudum , Festuca sinensis , and Bromus inermis seeds [28]. Studies on Sorghum sudanense seeds show that the semipermeable layer is located on the inner side of the aleurone layer, close to the undifferentiated cells, and is, hence, endospermic [29].…”
Section: Discussionmentioning
confidence: 99%
“…The semipermeable layer is firmly attached on the external portion of the seed coat in Roegneria nutans , Achnatherum inebrians , Hordeum vulgare var. nudum , Festuca sinensis , and Bromus inermis seeds [28]. Studies on Sorghum sudanense seeds show that the semipermeable layer is located on the inner side of the aleurone layer, close to the undifferentiated cells, and is, hence, endospermic [29].…”
Section: Discussionmentioning
confidence: 99%
“…This was because the seeds produced phenol and siderophores compounds that it can adhere to the surface of the seed coat that was semipermeable and bound to the seed coat that induces systemic plant resistance. Zhou et al (2013) reported that tomato seed coat was semipermeable and composed of fat, pectin, and cellulose, this was evidenced by coloring techniques and histochemical analysis because phenol and siderophores compounds in seeds indicate that the molecules of these compounds are chemically bound to fat molecules, pectin, cellulose. Moreover, another reason is that phenol and siderophore that bind to the seed elicit resistance gen of solanaceae plants against R. solanacearum and effectiveness of inducing systemic plant resistance.…”
Section: In Planta Assaymentioning
confidence: 99%
“…nudum contains lipids in the semipermeable layer of seed coat [9]. F. sinensis seed coat has pectine and seed coat.…”
Section: Antagonistic Test In Vitromentioning
confidence: 99%